COVID-19 Patients' Satisfaction Levels with Nursing Care: A Cross-Sectional Study - Fahad Alhowaymel PhD, RN; Abdulaziz Abaoud MSN, RN; Abdullah Alhuwaimel BSN, RN; Atallah Alenezi PhD, RN; Nahed Alsayed PhD, RN (SAGE Publishing, 2022)
Introduction COVID-19 is the most recent coronavirus diseases that was first identified in December 2019 and began its exponential spread globally. The critical role of nurses can be severely impacted during pandemics such as COVID-19 when the world is less prepared. Objective To investigate and measure COVID-19 patients' satisfaction levels with the quality of nursing care provided in the Riyadh Province of Saudi Arabia. Methods The study used a cross-sectional questionnaire to collect data from COVID-19 patients who were hospitalized or quarantined for at least 48 h or more. The study utilized the Arabic version of the Patient Satisfaction with Nursing Care Quality Questionnaire (PSNCQQ-Ar) to assess patients' satisfaction levels with nursing care. Descriptive statistics, Mann-Whitney U, and Kruskal-Wallis tests were performed to examine the objectives of the study. Results Ninety-six patients reported relatively high satisfaction levels with the overall nursing care. Patients also reported high satisfaction levels with the provided care, and the information that was provided. There were statistically significant differences in the mean score of patients satisfaction in relation to age, educational level, where patients are originally from, and patients recommendation of the hospitals. Conclusions Individual characteristics and attributes played a role in the process of evaluating nursing care services. Measuring nursing care quality clarified the significant role of nurses during the COVID-19 pandemic. This study provides valuable information that could help in identifying weaknesses and reinforcing strengths about nursing care to be fully prepared against pandemics and other health-related crises and emergencies in the future.